Spheroidal first order polarization tensor calculator (SFOPT) - Mohamad Yunos, Nurhazirah; Ahmad Khairuddin, Taufiq Khairi; Ahmed Sukri, Suzarina; Ahmad Jamil, Nor shafiqah; Azman, Amirul Zaqwan; Ahmad Noor Azhari, Muhammad Adli Iskandar (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Polarization Tensor (PT) has been applied in various applications involving metal detection, electrical imaging, and the study of electrosensing fish. In these applications, PT is able to capture significant information, such as material, shape, and orientation about the related objects. Previous studies have shown that most objects can be related to ellipsoid. However, this project aims to focus on spheroids, which are prolate and oblate spheroids, such that they are two different types of ellipsoids. This project intends to invent a standalone application, namely the Spheroidal First Order Polarization Tensor Calculator (SFOPT). SFOPT will provide quick access to calculate the first order PT for a spheroid when the researcher enters required information, such as its semi axes and conductivity. Additionally, the size (also known as semi axes) of the spheroid can be determined from the given first order PT by fixing the conductivity of the spheroid. The application will act as a reference for the researcher to determine the first order PT of a spheroid and to obtain the size of the spheroid from a given first order PT.